SOCIOECONOMIC SUPPORT OF THE PRISTINE STATE OF SUPE-PERÚ: THE EVIDENCES OF CARAL-SUPE - Shady Solís, Ruth (2000)
The present article tries about the factors that made an unprecedented economic development in the Andean area until the Late Archaic period. The author postulates that the northcentral area of Perú (Supe valley) was the place where the first model of state (pristine state) settled. This conformed by the autodynamics of the societies that were in that area, to the development of productive forces and the strategic location Supe valley.